Generation and characterisation of four human NAD(P)HX epimerase (NAXE) knockout iPSC lines - Tim Sikora; Myrto Patraskaki; Sara Howden; Alison Graham; John Christodoulou; Carole L. Linster; Nicole J. Van Bergen (Stem Cell Research)
Pathogenic variants in NAD(P)HX epimerase (NAXE) cause early-onset progressive encephalopathy with brain edema and/or leukoencephalopathy-1 (PEBEL1), an ultra-rare severe neurometabolic disorder resulting in death in infancy. The absence of functional NAD(P)HX epimerase leads to accumulation of S- and R-forms of NAD(P)HX, inhibiting key metabolic pathways. We have generated four NAXE-deficient cell lines via simultaneous CRISPR/Cas9-mediated gene knockout (KO) of NAXE and episomal reprogramming of control human fibroblasts into induced pluripotent stem cells (iPSCs). We have demonstrated loss of NAXE gene expression, characterized iPSC pluripotency and differentiation potential into three germ layers. This provides a suitable model for investigating disease mechanisms and therapies.